Simultaneous Determination of Ciprofloxacin and Ofloxacin in Animal Tissues with the Use of Capillary Electrophoresis with Transient Pseudo-Isotachophoresis - Izabella Kośka; Krystian Purgat; Rafał Głowacki; Paweł Kubalczyk (Molecules, 2021)
We have developed a precise and accurate method for the determination of ciprofloxacin and ofloxacin in meat tissues. Our method utilizes capillary electrophoresis with a transient pseudo-isotachophoresis mechanism and liquid–liquid extraction during sample preparation. For our experiment, a meat tissue sample was homogenized in pH 7.00 phosphate buffer at a ratio of 1:10 (tissue mass: buffer volume; g/mL). The extraction of each sample was carried out twice for 15 min with 600 µL of a mixture of dichloromethane and acetonitrile at a 2:1 volume ratio. We then conducted the electrophoretic separation at a voltage of 16 kV and a temperature of 25 °C using a background electrolyte of 0.1 mol/L phosphate–borate (pH 8.40). We used the UV detection at 288 nm. The experimentally determined LOQs for ciprofloxacin and ofloxacin were 0.27 ppm (0.8 nmol/g tissue) and 0.11 ppm (0.3 nmol/g tissue), respectively. The calibration curves exhibited linearity over the tested concentration range of 2 to 10 nmol/g tissue for both analytes. The relative standard deviation of the determination did not exceed 15%, and the recovery was in the range of 85–115%. We used the method to analyze various meat tissues for their ciprofloxacin and ofloxacin contents.